Flexible and Low-cost Production of Waveguide Based Integrated Photonic Devices. (2016) - Rahlves, Maik
Abstract: We present a process to fabricate fully polymer based integrated optical devices which is based on maskless lithography and hot embossing. Using the maskless lithographic setup, we are able to create a hot embossing stamp in a flexible and fast manner. We demonstrate that our process is capable of creating linear optical waveguides, Y-splitters and Mach-Zehnder interferometers designed by preliminary optical simulations. The fabricated structures are analyzed with respect to optical smoothness and line edge roughness. In the future, our process will greatly enhance a fast design and fabrication of complex optical sensor structures.